STUDY OF ELISA TEST-SYSTEMS OF DIFFERENT FORMATS FOR DETECTION OF MEASLES VIRUS SPECIFIC IgM IN DIFFERENT GEOGRAPHIC ZONES - M. A. Bichurina (Sankt-Peterburg : NIIÈM imeni Pastera, 2018)
Detection of the measles virus (MV) specific IgM antibodies in blood serum of patients is considered to be the main standard for the  laboratory confirmation of measles diagnosis, the test being  acknowledged by WHO. As it was demonstrated earlier the specific  IgM antibodies as the marker of the acute MV infection were  detected in 97.2–100% of blood serum samples from patients using  the ELISA test-systems of the “capture” format (Microimmun Ltd.  and Vector Best). In case when the ELISA test-system of the  “indirect” format (Siemens, Germany) was used only 63.9% of these sera turned to be IgM positive. And on the contrary using the  “indirect” format ELISA test-system Euroimmun, Germany, for  detection of the MV specific IgM the false positive results were  obtained.The aim of the study was the comparative evaluation of  the different format ELISA test-systems used for the detection of the  MV specific IgM antibodies in blood sera of patients and healthy  adults collected in different geographic zones.Materials and  methods. In total 108 serum specimens collected in 2015–2017 were studied: from healthy adult Guineans, residents of the Republic of Guinea (RG); patients aged 1–70 with the initial  “infectious mononucleosis”, “infectious cytomegalovirus” and  “rubella” diagnosis and taken from the bank of sera in the  Subnational Measles/Rubella laboratory, StP Measles/Rubella RC in  NWFR. The MV specific IgM antibodies were detected using the commercial ELISA test-systems “VectoMeasles-IgM” (Vector-Best,  Russia) (“capture” format) and “Anti-Measles Virus ELISA IgM (NP)”  (Euroimmun Medizinische Labordiagnostik AG, Germany) («indirect»  format). The specific Epshtein-Barr Virus (EBV) IgM and IgG  antibodies were detected with the commercial ELISA test-systems «DS-ELISA-anti-EBV-VCA-M», «DS-ELISA-anti-EBV-EA-G» and «DS-ELISA-anti-EBV-NA-G» (“Diagnostic Systems”, Russia).Results and discussion. The MV specific IgM antibodies were not revealed in the total of 108 blood serum samples from the healthy adults and patients, residents of the Russia and of the RG, with the “capture”  format “VectoMeasles-IgM” ELISA test-system. The absence of the  acute MV infection was also confirmed by the high measles immunity  level (i.e. IgG MV antibodies titers) as well as by detection of the IgG antibodies of high avidity. At the same time in 6  of 108 total sera (5.5%) IgM MV antibodies were detected with the «indirect» format ELISA test system Euroimmun, Germany. In these 6 sera the EBV specific antibodies were also evidenced. The results  obtained demonstrate the nonspecific reaction due to the possible  reactivity with anti-EBV antibodies. Besides this the different  percentage of the false positive reactions in sera from healthy  adults, residents of the RG and residents of Russia was determined  — 8.5±4.0% and 3.2±2.2% correspondently. Thus the preliminary  results, and to get the final results for general conclusions increase  of the total amount of the clinical specimens under studying is of extremely importance.